What’s new in cardiac amyloidosis? Pharmacological treatment, physical activity, and care of patients with transthyretin cardiac amyloidosis - Ezequiel J. Zaidel; Sol C. Song; Juan J. Sterba; Agustina Piccinato; María Candelaria Ramos; Silvina L. Cacia (Therapeutic Advances in Cardiovascular Disease, 2024)
Awareness, proper diagnosis and treatment of cardiac amyloidosis have increased, but there are still several unmet needs that have to be addressed for the optimal care of the disease. In this comprehensive review, we describe current and future treatments for both hereditary and wild-type TTR cardiac amyloidosis and also review lifestyle, including current challenges and opportunities for specific dietary concerns and exercise sports for these patients.